Alteration of gut microbiota after heat acclimation may reduce organ damage by regulating immune factors during heat stress - Liu, Shanshou; Wen, Dongqing; Feng, Chongyang; Yu, Chaoping; Gu, Zhao; Wang, Liping; Zhang, Zhixiang; Li, Wenpeng; Wu, Shuwen; Liu, Yitian; Duan, Chujun; Zhuang, Ran; et al. (Frontiers in Microbiology, 2023)
Heat-related illnesses can lead to morbidity, which are anticipated to increase frequency with predictions of increased global surface temperatures and extreme weather events. Although heat acclimation training (HAT) could prevent heat-related diseases, the mechanisms underlying HAT-promoting beneficial changes in organ function, immunity, and gut microbes remain unclear. In the current study, we recruited 32 healthy young soldiers and randomly divided them into 4 teams to conduct HATs for 10 days: the equipment-assisted training team at high temperature (HE); the equipment-assisted training team under normal hot weather (NE); the high-intensity interval training team at high temperature (HIIT), and the control team without training. A standard heat tolerance test (HTT) was conducted before (HTT-1st) and after (HTT-2nd) the training to judge whether the participants met the heat acclimation (HA) criteria. We found that the participants in both HE and NE teams had significantly higher acclimation rates (HA/total population) than whom in the HIIT team. The effects of HAT on the participants of the HE team outperformed that of the NE team. In the HA group, the differences of physiological indicators and plasma organ damage biomarkers (ALT, ALP, creatinine, LDH, a-HBDH and cholinesterase) before and after HTT-2nd were significantly reduced to those during HTT-1st, but the differences of immune factors (IL-10, IL-6, CXCL2, CCL4, CCL5, and CCL11) elevated. The composition, metabolism, and pathogenicity of gut microbes changed significantly, with a decreased proportion of potentially pathogenic bacteria (Escherichia-Shigella and Lactococcus) and increased probiotics (Dorea, Blautia, and Lactobacillus) in the HA group. Training for a longer time in a high temperature and humidity showed beneficial effects for intestinal probiotics. Therefore, pathogenic gut bacteria decrease while probiotics increase following HA, with elevated immune factors and reduced organ damage during heat stress, thereby improving the body's heat adaption.